AI sebagai Pendamping Guru PAI (Telaah Nilai Tarbiyah, Ta’lim, dan Ta’dib di Era Digital): AI, TARBIYAH, TA'LIM DAN TA'DIB - Ahmad, Arbi Salam; Kustati, Martin; Bashori, Bashori (Indo-MathEdu Intellectuals Journal, 2025)
The rapid advancement of AI technology offers opportunities to improve learning effectiveness but also poses challenges in preserving the moral and spiritual values that underpin Islamic education. This study aims to analyze the role of Artificial Intelligence (AI) as a companion to Islamic Religious Education (PAI) teachers through the perspectives of tarbiyah, ta’lim, and ta’dib. The research uses a descriptive qualitative method with a literature study approach, drawing on national and international journal articles, books, policy reports, and classical Islamic educational references. Source selection was based on relevance and a publication range from the last ten years (2015–2025). Data were collected through documentation techniques by accessing academic databases and scientific portals. The data were analyzed using content and thematic analysis through stages of data reduction, issue categorization, synthesis of findings, and conceptual interpretation. The results show that AI can support ta’lim by providing adaptive learning, digital tutoring, and automated assessment, yet it cannot fulfill the functions of tarbiyah and ta’dib due to its lack of emotional sensitivity, ethical awareness, and spiritual depth. Therefore, the role of teachers as murabbi remains essential. The study concludes that AI serves as a pedagogical partner that strengthens learning and must be integrated in alignment with Islamic values